SOCIO-PSYCHOLOGICAL PECULIARITIES OF EXPERIENCE BY MEN AND WOMEN OF CRISIS OF THE «EMPTY NEST» - V. V. Kozyreva (Вестник университета)
The results of the study of the experience of the crisis of the «empty nest» in women and men have been presented. The interrelations of subjective feeling of loneliness and characteristics of family relations and life orientations in men and women, experiencing the crisis of «empty nest» have been revealed. Levels of subjective feeling of loneliness separately in group of husbands and wives have been studied. Significant differences in the experience of the «empty nest» crisis depending on education and living together separately from children have been highlighted. Psychological recommendations for prevention of parents’ maladjustment in the situation of «empty nest» have been given.